Mendelian randomization analysis identified potential genes pleiotropically associated with gout - Wang, Yu; Chen, Jiahao; Yao, Hang; Li, Yuxin; Xu, Xiaogang; Zhang, Delin (Frontiers in Genetics, 2024)
This study aims to prioritize genes potentially involved in multifactorial or causal relationships with gout.Using the Summary Data-based Mendelian Randomization (SMR) approach, this research analyzed expression quantitative trait loci (eQTL) data from blood and renal tissues and genome-wide association study (GWAS) data related to gout. It sought to identify genetic loci potentially involved in gout. Heterogeneity testing was conducted with the HEIDI test, and results were adjusted for the False Discovery Rate (FDR).Blood cis-eQTL data were sourced from the eQTLGen Consortium's summary-level data, and renal tissue data came from the V8 release of the GTEx eQTL summary data.Gout GWAS data was sourced from the FinnGen Documentation of the R10 release.SMR analysis identified 14 gene probes in the eQTLGen blood summary-level data significantly associated with gout. The top five ranked genes are: ENSG00000169231 (labeled THBS3, PSMR = 4.16×10 -13 ), ENSG00000231064 (labeled THBS3-AS1, PSMR = 1.88×10 -8 ), ENSG00000163463 (labeled KRTCAP2, PSMR = 3.88×10 -6 ), ENSG00000172977 (labeled KAT5, PSMR = 1.70×10 -5 ), and ENSG00000161395 (labeled PGAP3, PSMR = 3.24×10 -5 ). Notably, increased expression of KRTCAP2 and PGAP3 is associated with an increased risk of gout, whereas increased expression of THBS3, THBS3-AS1, and KAT5 is associated with a reduced gout risk. No significant gene associations with gout were observed in renal tissue, likely due to the limited sample size of kidney tissue.Our findings have highlighted several genes potentially involved in the pathogenesis of gout. These results offer valuable insights into the mechanisms of gout and identify potential therapeutic targets for its treatment.